1995
DOI: 10.1093/ajcp/104.5.547
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus anginosus, Streptococcus constellatus and Streptococcus intermedius Clinical Relevance, Hemolytic and Serologic Characteristics

Abstract: A collection of 518 "Streptococcus milleri" isolates recovered from clinical specimens was identified to the species level according to recently established criteria. Streptococcus anginosus was the most frequently isolated species (59.3%), followed by S constellatus (30.3%) and S intermedius (10.4%). One third (34%) of all isolates were /3-hemolytic. The majority of S anginosus isolates were nonhemolytic, carried I.ancefield group F, or were nongroupable. Most of the 5 constellatus isolates were /3-hemolytic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
3
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 12 publications
5
75
3
1
Order By: Relevance
“…Most diagnostic laboratories use sheep or horse blood agar to screen for haemolysis and this may explain the paradoxical fact that non-haemolytic SMG strains have been found to be more associated with purulent infections than the â-haemolytic SMG strains [8,9]. Indeed, from the present data, many of the non-(sheep) haemolytic SMG strains encountered in diagnostic practice represented S. intermedius strains that invariably expressed haemolysis against human RBC without affecting animal RBC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Most diagnostic laboratories use sheep or horse blood agar to screen for haemolysis and this may explain the paradoxical fact that non-haemolytic SMG strains have been found to be more associated with purulent infections than the â-haemolytic SMG strains [8,9]. Indeed, from the present data, many of the non-(sheep) haemolytic SMG strains encountered in diagnostic practice represented S. intermedius strains that invariably expressed haemolysis against human RBC without affecting animal RBC.…”
Section: Discussionmentioning
confidence: 78%
“…milleri' strains to be associated with purulent disease more frequently than non-haemolytic strains [6,7], but this association was not found by others [8]. A study of 499 SMG clinical strains consecutively isolated irrespective of their haemolytic behaviour found that non-haemolytic strains were isolated more frequently from abscess-related specimens than â-haemolytic strains [9]. Furthermore, it found that the S. intermedius phenotype was proportionally more associated with infection and abscesses than the S. anginosus and S. constellatus phenotypes.…”
Section: Introductionmentioning
confidence: 98%
“…Similar conclusions have also been reached by other workers using the filter method for DNA hybridization (Kilpper-Balz et al, 1984). The DNA homology data, together with the phenotypic differentiation of S. anginosus, S. constellatus and S. intermedius (Whiley & Beighton, 1991;Ahmet et al, 1995;Jacobs e f al., 1995) and the strong clinical association patterns for these taxa (Whiley et al, 1992;Jacobs et al, 1995), refute the idea that these constitute a single species. The evidence reported in this paper supports the further subdivision of S. constellatus into two subspecies.…”
Section: Discussionmentioning
confidence: 92%
“…Collectively, these form part of the flora of the mouth and the female urogenital tract, are isolated from the gastrointestinal tract, and are frequently associated with purulent infections in humans (Whiley et al, 1992;Jacobs et al, 1995). Evidence of further taxonomic heterogeneity within the group has been supported by phenotypic and genotypic criteria that include biochemical and cultural characteristics (Winstanley et al, 1992 ;Bergman et al, 1995), long-chain fatty acid composition (Cookson et al, 1989), pyrolysis mass spectra (Winstanley et al, 1992), DNA hybridization (Whiley & Hardie, 1989;Whiley et al, 1997), and rRNA-based studies (Doitt et al, 1994;Bergman et al, 1995 anginosus were shown to exhibit sufficient heterogeneity to warrant division at both species and subspecies level, although the numbers of strains belonging to these taxa were too few to support any formal taxonomic proposals (Whiley et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…AGS are recognized as opportunistic pathogens that cause purulent infection and abscess formation (6,16,32,(37)(38)(39). Notably, S. intermedius is an important pathogen of humans frequently causing deep-seated infections including abscesses in the brain and liver (38,39 Abstract: Streptococcus intermedius causes endogenous infections leading to abscesses.…”
mentioning
confidence: 99%